Sistem Pendukung Keputusan Untuk Seleksi Penyedia Pengadaan Barang Dan Jasa Di Departemen Pekerjaan Umum Direktorat Jendral Sumber Daya Air Yogyakarta - Wahyudi .; dahlan susilo; Mochtar Yunianto (Universitas Sahid Surakarta, 2010)
Selection of providers of goods and services is a routine work carried out by the Ministry of Public Works Directorate General of Water Resources (DPU DirJen SDA) Yogyakarta as auctioneer project procurement. The auction process conducted by 2 steps that must be passed by each participant selection, namely the pre-selection andselection process. Pre-selection stage takes a long time from the announcement of the project which will be auctioned to the technical bid evaluation assessment of participant selection document roadmap participants. The next stage of the selection process, this process will not work if the previous stage of the selection of participants who did not pass the next phase still could not accept the results of the selection committee on the assessment of the value of the technical evaluation of bids that have been made by the participant selection, because the rule is no objection period provided to participants if the selection can not accept the results of the assessment selection committee. The selection process will run to the next stage after the selection of participants receiving the results of the assessment of the selection committee and given objection period had expired. Based on the background of the existing problems can be formulated on how to make a design decision support system for the selection of providers of goods and services in DPU DirJen SDAYogyakarta. The decision support system aims to implement a decision support system for the selection of goods and services providers to the selection committee in DPU DirJenSDA Yogyakarta. The system works based on the data input of the selection committee which will then be processed by the system based on the required criteria. The data has been processed the system will be displayed and ranked by graphs of each participant selection. From these results we can conclude the committee which participantsprocurement of goods and services providers are entitled to handle the project.